2022
DOI: 10.1029/2022jg006980
|View full text |Cite
|
Sign up to set email alerts
|

Subsurface Lateral Flows Buffer Riparian Water Stress Against Snow Drought

Abstract: In the Sierra Nevada, CA, the Mediterranean climate exposes montane forests to water stress during the summer drought. Normally, spring snowmelt alleviates summer water stress, especially in riparian ecosystems that receive subsurface lateral inputs from groundwater. However, snow drought could potentially eliminate these beneficial effects. This research investigates how subsurface lateral redistribution mediates hillslope‐scale vegetation responses to snow drought. We apply a spatially‐distributed ecohydrolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 118 publications
0
4
0
Order By: Relevance
“…The dynamic observed by Martin et al (2018)s supports a view of hillslope ecohydrology where subsurface connections increase downslope and this determines water use patterns in a way that may supersede species traits (Brooks et al, 2015). However, it also should be noted that elevational position along the hillslope may be less important to forest water use than sub-hillslope context such as proximity to local convergence zones where surface connections to groundwater are locally critical to support tree water demand (Hoylman et al, 2018;Graup et al, 2022). In contrast, other studies have found limited differences in water use patterns across the hillslope reflecting multiple interacting influences emerging from species traits, stand properties and hillslope hydrology that ultimately mute gradients in sensitivities to changing precipitation inputs (Fabiani et al, 2022).…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…The dynamic observed by Martin et al (2018)s supports a view of hillslope ecohydrology where subsurface connections increase downslope and this determines water use patterns in a way that may supersede species traits (Brooks et al, 2015). However, it also should be noted that elevational position along the hillslope may be less important to forest water use than sub-hillslope context such as proximity to local convergence zones where surface connections to groundwater are locally critical to support tree water demand (Hoylman et al, 2018;Graup et al, 2022). In contrast, other studies have found limited differences in water use patterns across the hillslope reflecting multiple interacting influences emerging from species traits, stand properties and hillslope hydrology that ultimately mute gradients in sensitivities to changing precipitation inputs (Fabiani et al, 2022).…”
Section: Introductionmentioning
confidence: 53%
“…The primary goal of this study was to test whether the sensitivity of widespread Rocky Mountain tree species to changing snowpack is related to reliance on snowmelt as a primary water source (Graup et al, 2022;Tague and Peng, 2013;Strange et al). Although many studies have independently tracked water sources by trees with stable isotopes spatially (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Short‐duration heavy rainstorm events driven by typhoon exerted a pulsing control mainly on groundwater level and soil moisture content (Sawyer et al, 2014; Shih et al, 2018; Zhang et al, 2022). Total amount and duration of monsoon‐controlled precipitation shaped water‐table rise, producing vertical linkage with unsaturated zone and lateral linkage with stream water in riparian zones (Graup et al, 2022; Scaife et al, 2020). Soil moisture content variations of middle and deep layers were closely related to groundwater level fluctuations (Figures 3b,c and 9e,f), because water table usually fluctuated near these two layers.…”
Section: Discussionmentioning
confidence: 99%